2014
DOI: 10.1002/2013jg002420
|View full text |Cite
|
Sign up to set email alerts
|

The use of radiocarbon to constrain current and future soil organic matter turnover and transport in a temperate forest

Abstract: (2014), The use of radiocarbon to constrain current and future soil organic matter turnover and transport in a temperate forest, J. Geophys. Res. Biogeosci., 119, 372-391, doi:10.1002 Abstract We investigated the merits of radiocarbon measurements for estimating soil organic matter (SOM) turnover and vertical transport for a temperate deciduous forest in Germany. Eleven parameters, defining decomposition and transport in the soil carbon model SOMPROF, were estimated using a Bayesian approach based on organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 97 publications
(105 reference statements)
1
39
0
Order By: Relevance
“…Our previous work with CLM4.5 showed that these resolved controls are insufficient to predict both observed total C and 14 C SOM profiles in temperate soils (23). This result is consistent with some (34), but not all (35), recent modeling analyses using similar vertically resolved carbon decomposition models. To address this issue, we defined in CLM4.5 an e-folding distance, Z τ , that modifies HR by decreasing the respiration flux from each pool as an exponential function of depth (23).…”
Section: Methodssupporting
confidence: 88%
“…Our previous work with CLM4.5 showed that these resolved controls are insufficient to predict both observed total C and 14 C SOM profiles in temperate soils (23). This result is consistent with some (34), but not all (35), recent modeling analyses using similar vertically resolved carbon decomposition models. To address this issue, we defined in CLM4.5 an e-folding distance, Z τ , that modifies HR by decreasing the respiration flux from each pool as an exponential function of depth (23).…”
Section: Methodssupporting
confidence: 88%
“…For example, soil organic matter should be represented as vertically resolved (Braakhekke et al, 2011(Braakhekke et al, , 2014Koven et al, 2015;Beer, 2016), with different soil carbon pools and a moisturedependent decomposition. Furthermore, the site hydrology should include soil moisture contents above field capacity and standing water above the surface (Stacke and Hagemann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, the resulting total CH 4 emissions with the three tested snow threshold depths were not statistically different. The JSBACH-methane model does not explicitly consider some mechanisms related to the 930 carbon decomposition and thaw in Arctic permafrost and wetland ecosystems, such as: CH 4 production in the soil from root exudates (Knoblauch et al, 2016;Ström et al, 2012), vertical transfer of carbon and its vertically resolved decomposition (Braakhekke et al, 2011(Braakhekke et al, , 2013(Braakhekke et al, and 2014Koven et al, 2015), and microbial community dynamics (McCalley et al, 2014) involved in anoxic CH 4 oxidation or the production of CH 4 in anaerobic microsites confined 935 in oxic soils. Although these processes might contribute substantially to the dynamics of CH 4 , research on these processes in soil-permafrost and wetland environments is still lacking or poorly understood with controversial results so far (Bridgham et al, 2013).…”
Section: Model Spatial Heterogeneitymentioning
confidence: 99%
“…KCM wishes to thank Andrew Durso for the English proofread of this manuscript. (Braakhekke et al, 2011;Braakhekke et al, 2014;Braakhekke et al, 2013;Koven et al, 2015;Sachs et al, 2010;Wille et al, 2008;Xu et al, 2016) Tuomi et al, 2009) 1290 Table 2. Daily methane emissions for the individual transport pathways and total methane emissions are shown.…”
Section: Acknowledgementsmentioning
confidence: 99%